Biogeochemical limitations of carbon stabilization in forest subsoils. Issue 1 (17th October 2021) - Liebmann, Patrick; Mikutta, Robert; Kalbitz, Karsten; Wordell‐Dietrich, Patrick; Leinemann, Timo; Preusser, Sebastian; Mewes, Ole; Perrin, Eike; Bachmann, Jörg; Don, Axel; Kandeler, Ellen; Marschner, Bernd; et al.
Abstract: Background: Soils are important carbon (C) sinks or sources and thus of utmost importance for global carbon cycling. Particularly, subsoils are considered to have a high potential for additional C storage due to mineral surfaces still available for sorptive stabilization. Aims: Little information exists about the extent to which additional litter‐derived C is transferred to and stabilized in subsoils. This study aimed at evaluating the role of litter‐derived dissolved organic matter (DOM) inputs for the formation of stable mineral‐associated C in subsoils. Methods: We carried out a multiple‐method approach including field labeling with 13 C‐enriched litter, exposure of 13 C‐loaded reactive minerals to top‐ and subsoils, and laboratory sorption experiments. Results: For temperate forest soils, we found that the laboratory‐based C sink capacity of subsoils is unlikely to be reached under field conditions. Surface C inputs via litter leachates are little conducive to the subsoil C pool. Only 0.5% of litter‐derived C entered the subsoil as DOM within nearly 2 years and most of the recently sorbed C is prone to fast microbial mineralization rather than long‐term mineral retention. Desorption to the soil solution and an adapted microbial community re‐mobilize organic matter in subsoils faster than considered so far. Conclusions: We conclude that the factors controlling the current mineral retention and stabilization of C within temperate forest subsoils will likewise limit additional C uptake. Thus, in contrast to their widely debated potential to accrue more C, the role of forest subsoils as future C sink is likely overestimated and needs further reconsideration.